2014
DOI: 10.1108/mhrj-05-2014-0015
|View full text |Cite
|
Sign up to set email alerts
|

Suicide risk in the UK trans population and the role of gender transition in decreasing suicidal ideation and suicide attempt

Abstract: Purpose -The purpose of this paper is to present findings from the Trans Mental Health Study (McNeil et al., 2012) -the largest survey of the UK trans population to date and the first to explore trans mental health and well-being within a UK context. Findings around suicidal ideation and suicide attempt are presented and the impact of gender dysphoria, minority stress and medical delay, in particular, are highlighted. Design/methodology/approach -This represents a narrative analysis of qualitative sections of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
63
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(73 citation statements)
references
References 18 publications
3
63
1
Order By: Relevance
“…Transgender is an umbrella term that describes anyone: ‘…whose gender expression or identity differs from societal expectations of their assigned sex at birth’ (Bailey et al . , p. 209). It has been suggested that the size of the transgender community is ‘difficult to capture’ (Kritz , p. 12) and that data sources estimating the number of adults in this group are very rare (Gates , Harris ).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Transgender is an umbrella term that describes anyone: ‘…whose gender expression or identity differs from societal expectations of their assigned sex at birth’ (Bailey et al . , p. 209). It has been suggested that the size of the transgender community is ‘difficult to capture’ (Kritz , p. 12) and that data sources estimating the number of adults in this group are very rare (Gates , Harris ).…”
Section: Introductionmentioning
confidence: 97%
“…The experience of mental health problems by transgender people is significant (Bailey et al 2014). Therefore, the lack of attention to this aspect of health is surprising considering this group also experience high levels of stigmatization and discrimination in society that negatively affects their lives at home, in education and at work (McNeil et al 2012.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has indicated that transgender individuals who are farther along in their social gender transition report less distress (Bailey, Ellis, & McNeil, 2014; Blanchard, Steiner, & Clemmensen, 1985; Budge et al, 2013a; 2013b). Therefore, individuals who have socially transitioned might be better emotionally equipped to handle any stigma that may result from experiencing changes in attractions.…”
Section: Introductionmentioning
confidence: 99%
“…Given the structural dominance of gender in society, trans people have a heightened consciousness of the extent to which their bodies and physical presentation do or do not confirm to gender norms. While trans people are at significant risk of transphobic victimisation, recent studies have shown that they have a heightened perception of this risk (Ellis, Bailey & McNeil, 2016) and go to great lengths to avoid being victimised (Ellis, McNeil & Bailey, 2014). In addition to social stigma, there are a number of personal challenges that trans people need to negotiate which also have a negative bearing on mental health and wellbeing.…”
mentioning
confidence: 99%